PERAN DAN KEWAJIBAN TENAGA KESEHATAN DALAM MENJAGA RAHASIA MEDIS: STUDI LITERATUR - Gunawan Widjaja; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
This study aims to analyse the role and obligations of health workers in maintaining medical confidentiality based on a literature review of regulations and practices in Indonesia. Medical confidentiality is a fundamental right of patients guaranteed by various laws and regulations and professional codes of ethics. This study employs a literature review method, examining primary and secondary legal sources such as laws, government regulations, ministerial regulations, as well as scientific journals and related articles. The results of the study indicate that the obligation to maintain medical confidentiality applies to all healthcare workers, including doctors, nurses, and other healthcare professionals, even after the patient's death. The implementation of medical confidentiality principles faces challenges in the digital age, such as the risk of data breaches and misuse of information, necessitating the strengthening of data security systems and continuous education for healthcare workers. Violations of this obligation may result in legal consequences, including criminal, civil, administrative, and ethical sanctions. Therefore, the protection of medical confidentiality must be a shared commitment between healthcare professionals and healthcare institutions to maintain patient trust and improve the quality of healthcare services.